High-Performance Thermoelectric Paper Based on Double Carrier-Filtering Processes at Nanowire Heterojunctions - Choi, Jaeyoo; Lee, Jang Yeol; Lee, Sang-Soo; Park, Chong Rae; Kim, Heesuk (WILEY-V C H VERLAG GMBH, 2016)
As commercial interest in flexible power-conversion devices increases, the demand for high-performance alternatives to brittle inorganic thermoelectric (TE) materials is growing. As an alternative, we propose a rationally designed graphene/polymer/inorganic nanocrystal free-standing paper with high TE performance, high flexibility, and mechanical/chemical durability. The ternary hybrid system of the graphene/polymer/inorganic nanocrystal includes two heterojunctions that induce double-carrier filtering, which significantly increases the electrical conductivity without a major decrease in the thermopower. The ternary hybrid shows a power factor of 143 mu W m(-1) K-1 at 300 K, which is one to two orders of magnitude higher than those of single-or binary-component materials. In addition, with five hybrid papers and polyethyleneimine (PEI)-doped single-walled carbon nanotubes (SWCNTs) as the p-type and n-type TE units, respectively, a maximum power density of 650 nW cm(-2) at a temperature difference of 50 K can be obtained. The strategy proposed here can improve the performance of flexible TE materials by introducing more heterojunctions and optimizing carrier transfer at those junctions, and shows great potential for the preparation of flexible or wearable power-conversion devices.
Keywords: CARBON NANOTUBES; ENHANCED THERMOPOWER; ORGANIC COMPOSITES; POLYMER; NANOCOMPOSITES; FILMS; POWER; CONDUCTIVITY; MORPHOLOGY; COMPLEX